New approaches to evacuation modelling for fire safety engineering applications. (June 2019) - Ronchi, Enrico; Corbetta, Alessandro; Galea, Edwin R.; Kinateder, Max; Kuligowski, Erica; McGrath, Denise; Pel, Adam; Shiban, Youssef; Thompson, Peter; Toschi, Federico
Abstract: This paper presents the findings of the workshop "New approaches to evacuation modelling", which took place on the 11th of June 2017 in Lund (Sweden) within the Symposium of the International Association for Fire Safety Science (IAFSS). The workshop gathered international experts in the field of fire evacuation modelling from 19 different countries and was designed to build a dialogue between the fire evacuation modelling world and experts in areas outside of fire safety engineering. The contribution to fire evacuation modelling of five topics within research disciplines outside fire safety engineering (FSE) have been discussed during the workshop, namely 1) Psychology/Human Factors, 2) Sociology, 3) Applied Mathematics, 4) Transportation, 5) Dynamic Simulation and Biomechanics. The benefits of exchanging information between these two groups are highlighted here in light of the topic areas discussed and the feedback received by the evacuation modelling community during the workshop. This included the feasibility of development/application of modelling methods based on fields other than FSE as well as a discussion on their implementation strengths and limitations. Each subject area is here briefly presented and its links to fire evacuation modelling are discussed. The feedback received during the workshop is discussed through a set of insights which might be useful for the future developments of evacuation models for fire safety engineering. Highlights: Findings of a workshop on new approaches to evacuation modelling are presented. Five areas useful for evacuation modelling development are introduced. Feedback on the modelling ideas is reported. A roadmap for implementation of new approaches is drafted.